Prediction of equilibrium distributions of isotopologues for methane, ethane and propane using density functional theory. (1st October 2016) - Piasecki, Alison; Sessions, Alex; Peterson, Brian; Eiler, John
Abstract: Many previous studies have examined abundances of deuterium (D) and 13 C within small organic molecules. Recent advances in analytical instrumentation add the abilities to measure site-specific and multiply substituted isotopologues of natural organics. Here we perform first-principles calculations of the equilibrium distributions of 13 C and D in the volatile alkanes (including both single and multiple substitutions), as a guide to the interpretation of current measurements and as a basis for anticipating isotope effects that might be examined with future analytical techniques. The models we present illustrate several common themes of the isotopic structures of the small alkanes, including; temperature dependent enrichment of clumped isotope species, with amplitudes in the order D–D > 13 C–D > 13 C– 13 C; similarity in strength of such clumped isotope effects between different molecules (e.g., 13 C–D clumping is ∼5‰ enriched at 300 K in methane, ethane and propane); a ∼10× contrast between the amplitudes of stronger adjacent substitution of two heavy isotopes vs. weaker non-adjacent substitution; temperature-dependent site-specific fractionation of D and 13 C into interior positions of molecules relative to terminal methyl groups; and a relatively simple additive effect to the overall amplitude of enrichment when clumped and site specific effects combine in the same isotopologue. We suggest that the most promising tools suggested by our results are isotopic thermometers based on site-specific distribution of deuterium, which exhibits strong (∼100‰), highly temperature dependent fractionation between methyl groups and methylene carbon positions in propane (and likely other larger n -alkanes).